Die Landschaft von Pontresina (Oberengadin) im Luftbild - Holtmeier, Friedrich-Karl (ERDKUNDE, 1969)
Using an air photograph, the author seeks to convey an impression of Nature and, above all, the reciprocal relationships between Nature and Man in the central Alpine high-valley region of Pontresina. The high-mountain climate, the great altitude of the valley-floors and the glacially-moulded relief conditions of this area do not leave Man much room for maneouvre in the vertical plane and force him to adjust as best he can to natural factors. On the steep, partly rocky trough walls stretch woodland areas, opened up by avalanches, mud-streams and rock falls. Where the terrain is suitable for alpine meadows on the flatter sloping trough shoulders and terraces, Man has cleared the woodland. The altitude of the upper woodland limit is, in the area shown on this air photograph, mostly orographically, but sometimes anthropogenically, determin ed. Pontresina, which formerly lived from alpine grazing, arable farming and, above all, traffic on the pass, lies on the south-west exposed slope of the Bernina Valley somewhat above the valley floor, which is made climatically unfavourable by frequent formation of cold air layers. In addition the insolation duration is substantially greater in the valley widening which begins here than in the upper part of the Valley. The lowest valley section has the largest amount of sunshine but was, like the still distinguishable gaps between the old village cores, never built on because of the avalanche danger. Tourism, today the basis of existence for the population nevertheless necessitates expansion of the village, houses have been built in these places, and some of them have already been buried by various small avalanches. A winter of avalanches, such as occurred in 1951, would bring catastrophe to these new village areas. A danger for the village which should not be underestimated is posed by the increasing amount of climbing damage on the slopes of the Schafberg and Piz Albris, caused by the immense population of ibexes (Capra ibex) in this area. The destruction of plant cover in the alpine region by these animals is followed by solifluction, initiated by needle ice (Kammeis, pipkrake, ice-filaments), at nearly all those places, which favour the formation of mud-streams (“Rüfen, “Muren) on these slopes.